Experimental glaucoma model (ischemia and reperfusion): histology, morphometry, protein and gene espression of apoptosis pathway - Zanoni, Diogo Sousa [UNESP] (2015)
Purpose: The aims of this study were to better understand the mechanism of cell death by apoptosis in a glaucoma model (ischemia / reperfusion) and evaluate the role of apoptosis in this model and if treatment with Sildenafil helps prevent apoptosis. Methods: 36 rats, from 4 to 6 months, males, Lewis and weighing ± 350g were divided in 5 groups: control group (6 animals) and for groups with ischemia / reperfusion (7 and 21 days), two groups consisting of ten animals treated with sildenafil and two groups of Five animals treated with placebo. Paracentesis of the anterior chamber with needle 30G coupled to saline (0.9%) was made and maintained for 60 minutes. Intraocular pressure was measured by rebound tonometer (Tonovet®). There was histological, morphometric by hematoxylin and eosin and, immunohistochemical staining and qRT-PCR analysis by Caspase-7, Caspase-6, Caspase-9, Tnf-r2, Fas-l, Bcl-2 and Bax. For statistic analysis we used ANOVA and t-test for morphometric analysis and, for immunohistochemistry and qRT-PCR, Fisher exact test was employed with a statistical significance level of p <0.05 Results: Histology and morphometric analysis, proved more changes in the untreated group compared to the treatment and control group. Analysis of immunohistochemistry and qRT-PCR observed the more significant expression in untreated eyes. Conclusion: Sildenafil apperead to be protective to ganglion cell apoptosis. Cell survival was evident in histology and morphometry. For immunohistochemistry and RT-PCR was observed protective effect in the apoptosis pathways with similar or below expression compared to the control